Etiological profile of early neonatal bacterial sepsis by multiplex qPCR - Silva-Junior, Walter P; Martins, Almir S; Xavier, Paula C N; Appel, Kelly L A; Oliveira Junior, Silvio A; Palhares, Durval B (The Journal of Infection in Developing Countries, 2016)
Introduction: Given the major impact in terms of morbidity and mortality that episodes of early neonatal sepsis (ENS) have on both newborns and health systems, this study aimed to identify the etiological profile of early neonatal bacterial sepsis by a multiplex quantitative real-time polymerase chain reaction (qPCR). Methodology: Blood samples from newborns diagnosed with clinical ENS and hospitalized in neonatal intensive care units (NICUs) were collected and analyzed using the multiplex qPCR method to detect Streptococcus agalactiae, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Enterobacter sp., Serratia sp., and Staphylococcus aureus. A universal primer was used in the analysis. Results: A total of 150 neonates with clinical sepsis and 10 newborns as healthy controls were included in the study. The group with clinical sepsis was 100% positive for the presence of bacterial genomic DNA through the universal primer. The control group showed negativity by qPCR. The multiplex qPCR analysis showed that 76% of the samples were positive for Escherichia coli, 34% for Staphylococcus aureus, 13.3% for Streptococcus agalactiae, 7.3% for Pseudomonas aeruginosa, and 0.7% for Enterobacter sp. and Serratia sp. Multiplex qPCR of patients with clinical sepsis matched with 8.1% of the blood samples that tested positive by the microbiological method. Conclusions: Rapid and sensitive detection of the pathogens causing ENS by this new multi-target approach based on multiplex qPCR could potentially excel compared to microbiological methods, with the simple objective of facilitating the progression to a more rapid and specific antimicrobial therapy, avoiding the abuse of antibiotics in NICUs.